1. Hu S, Sprintall J, Guan C, et al. Deep-reaching acceleration of global mean ocean circulation over the past two decades. Sci Adv. 2020;6(6):eaax7727. - Shijian Hu; Wenju Cai (TheScienceBreaker, 2020)
Platelet dysfunction drives bleeding complications in patients with advanced chronic kidney disease (CKD), worsening clinical outcomes. However, the underlying mechanisms remain unclear, limiting treatment options. In this study, we identified the expression of urea transporter B (SLC14A1/UT-B) in human and mouse platelets. By analyzing a clinical cohort of patients with CKD, we demonstrated that single-nucleotide polymorphisms in SLC14A1 were associated with bleeding events in CKD. Using a 5/6 nephrectomy (5/6 Nx) mouse model and blood samples from patients with advanced CKD, we found that SLC14A1/UT-B-mediated urea influx underlies platelet dysfunction in advanced CKD given that both genetic knockout of Slc14a1 or pharmacological inhibition of UT-B reversed mouse and human platelet dysfunction induced by urea or advanced CKD plasma. SLC14A1/UT-B-mediated urea influx induced protein carbamylation, which drove platelet dysfunction. By characterizing the carbamylation profiles of proteins in human and mouse platelets, we demonstrated that carbamylation disrupted cytoskeletal rearrangement, degranulation, and inside-out integrin αIIbβ3 signaling transduction during platelet activation, leading to impaired platelet aggregation, secretion, and spreading in advanced CKD. Furthermore, treatment of 5/6 Nx mice with the UT-B inhibitor PU-48 effectively preserved platelet function and improved hemostatic ability. These findings suggest that SLC14A1/UT-B promoted urea uptake in platelets and mediated bleeding in advanced CKD, highlighting its potential as a therapeutic target for managing bleeding complications in patients with advanced CKD.